2020
DOI: 10.1590/0034-7167-2019-0143
|View full text |Cite
|
Sign up to set email alerts
|

Presumption of sexual abuse in children and adolescents: vulnerability of pregnancy before 14 years

Abstract: Objectives: to investigate the presumption of sexual abuse through the records of live births with mothers up to 13 years of age. Methods: this is a quantitative study, with an ecological design, carried out in Maceió, with data from the Brazilian Live Birth Information System from 2009 to 2017, based on Law 12,015/2009, on sexual crimes against the vulnerable, applying the presumption of violence in children under 14 years old. Results: nine hundred fifty-three births of children with mothers aged 10 to 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
(19 reference statements)
1
6
0
4
Order By: Relevance
“…The mean of 13.6 years old for sexual initiation among the adolescents in this study corroborates the data found in a survey conducted with public school students in Pouso Alegre, Minas Gerais, who presented a mean of 13.8 years old 18 . In addition, male adolescents initiate sexual activities earlier and present more relationships experienced, when compared to the female gender 9 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The mean of 13.6 years old for sexual initiation among the adolescents in this study corroborates the data found in a survey conducted with public school students in Pouso Alegre, Minas Gerais, who presented a mean of 13.8 years old 18 . In addition, male adolescents initiate sexual activities earlier and present more relationships experienced, when compared to the female gender 9 .…”
Section: Discussionsupporting
confidence: 89%
“…To understand vulnerability issues related to the ESI process among male adolescents attending school in a context of gender diversity, anchorage in Leininger's Transcultural Theory emerges. This theory considers the historical, political and sociocultural aspects as essential to consolidate an integral health care proposal with this population group, 12 the bio-psycho-socio-cultural development is under construction in this population segment 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Souto et al 5 compared the registers of rape of vulnerable with that of births from mothers aged <14 years and verified that only 4% were notified as sexual violence. A similar study 17 showed notifications only in 1.3% in the age group of 10-13 years.…”
Section: Discussionmentioning
confidence: 63%
“…The low notification by health professionals reveals that pregnancy in girls aged <14 years is not identified as resulting from sexual abuse, which highlights the invisibility of the problem 5,17 .…”
Section: Discussionmentioning
confidence: 99%
“…e gravidez indesejada(BARNERT et al, 2017;CERÓN- HERNÁNDEZ;ROA-TORRES;SALCEDO-CIFUENTES, 2017;FAUS et al, 2019;GUEDES et al, 2017;MASON-JONES;NICHOLSON, 2018;McALPINE;HOSSAIN;ZIMMERMAN, 2016;REID, 2018;TRINDADE;OLIVEIRA, 2020;TOLU;GUDU, 2020;ZIJLSTRA et al, 2017).…”
mentioning
confidence: 99%